CNN-based Binary and Categorical Model to Detect Tumor from MR Images - Datta, Aparna; Mukherjee, Pritam; Paul, Gourab (International Journal of Computer Sciences and Engineering, 2026)
Detecting Brain tumors through human eye inspection has a probability of errors in analysis and a higher number of MRI reports cannot be inspected in a feasible amount of time. Thus, we need an easier automated approach towards this, that can be easily used and can give accurate results in Tumor detection. In this paper, we have implemented a Machine Learning Model based on Convolutional Neural Network, with the help of Global Average Pooling to fulfill this goal. Here we have two models, where one can do a binary classification of the images to detect if they have a trace of tumor in the MR Images or not, and another model that can detect the type of Tumor categorically among 3 types which are Glioma, Meningioma, and Pituitary. This model has acquired an accuracy score of 96.02% and 99.46% in the Binary and Categorical Models respectively.